Global Central Limit Theorems for Stationary Markov Chains - Lin Michael (Annales Mathematicae Silesianae, 2025)
Let P be a Markov operator on a general state space (S, Σ) with an invariant probability measure m, assumed to be ergodic. We study conditions which yield that for every centered non-zero f ∈ L2(m) a non-degenerate annealed CLT and an L2-normalized CLT hold.